Welfare benefits and work incentives: An analysis of the distribution of net replacement rates in Europe using EUROMOD, a multi.country microsimulation model - Herwig Immervoll; Cathal O'Donoghue (University of Essex, Institute for Social and Economic Research (ISER), 2001)
This paper considers the methodology of measuring replacement rates, comparing simulation based approaches, which simulate replacement rates for a representative sample of the population, with other approaches that simulate replacement rates for typical families or are entirely based on recorded household data. We emphasise the advantages of the first method. Utilising a cross-country microsimulation model for Europe, EUROMOD, we generate the distribution of replacement rates for four European countries, Denmark, France, Spain and the UK. In particular we show the important role of household composition and the presence of other household members' incomes in preserving the standard of living while out of work. We argue that, given this strong influence of primary incomes, replacement rates are not necessarily the best indicator of the impact of the taxbenefit system in this respect. To isolate the effects of the tax-benefit system on both work incentives and the degree of social protection for the out-of-work population, we therefore introduce a new measure, the “tax-benefit-to-earnings ratio”.
Keywords: H31; J65; E60; C81; 330; Net Replacement Rate; Unemployment Benefits; Work Incentives; European Union; Microsimulation; Sozialhilfe; Arbeitslosenversicherung; Leistungsanreiz; Simulation; EU-Staaten